Dimensions of Ethical Accounting Practices among Certified Public Accountants: An Exploratory Factor Analysis - Niniel, Jaylou C.; Sucuahi, William T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research study explored and established the dimensions representing ethical accounting practices among Certified Public Accountants. The respondents were Certified Public Accountants from different sectors of the profession in Davao del Norte, of legal age and with at least two years of experience in accounting who were chosen through stratified random sampling. Responses from the Key Informant Interview were analyzed and the item statements were then used as initial statement pool for the survey. Kaiser-Meyer-Olkin (KMO) index for sampling adequacy, Bartlett’s test of sphericity for testing the multidimensionality, principal component analysis for data reduction, and VARIMAX for rotation. Thirty-one (31) original items were surveyed and processed through exploratory factor analysis and only twenty-six (26) items of ethical accounting practices passed the ≥.40 threshold after ten iterations which loaded to eight dimensions. The identified eight generated dimensions of ethical accounting practices were moral philosophies, personal values and principles, religiosity, objectivity, reliance to authority, integrity, professional behavior and public_welfare.